Analisis dan Pengukuran Kualitas Informasi Pada Website Menggunakan Pendekatan Six Sigma - Faisal, Bagus; Candiwan, Candiwan; Priyadi, Yudi (Universitas Diponegoro, 2018)
Information held by a company is one of the important factors for its success. Nowadays with rapid development of usage of internet and social media, bad information can also have a significantly negative impact on every element / level that exists in the company or in the community. Sometimes it can lead to public unrest. Bad or good information has correlation with the quality of information. The aim of this researchÂ is to assest and analyzeÂ the quality of information using Six Sigma approach and we choose Kaskus website as a case study. Kaskus is the largest community online in Indonesia. It provided various kinds of information to its user. By using its approach, this research consists of 5 stages, they are â€œdefineâ€, â€œmeasureâ€, â€œanalysisâ€, â€œimproveâ€, and â€œcontrolâ€. Each phase/stage using different tools to assess the current Information Quality, such as questionnaires for define phase, â€œExpert Choiceâ€(Analytic Hierarchy Process) for measure phase, and quality function deployment (QFD) for analysis stage. Questionnaires used for defining customer specifications and identify information quality problem, meanwhile software â€œExpert Choiceâ€ used to measure the importance each quality information dimensions and then to validate/analyzise the problem of the data. And lastly, QFD used to determine the mutual relationships of information quality dimensions and critical to Information Quality factors. Output of â€œAnalyzeâ€ stage shows that Accuracy, Relevancy, and Objectivity dimension on Kaskus website need to be improved immediately because it reaches unacceptable point.